Factors affecting the effectiveness/productivity of therapeutic plasma exchange in the treatment of immune-mediated neurologic disorders – a pilot study - Vraneš, Marija; Lazović, Aleksandar; Balint, Bela; Jakovljević, Vladimir; Todorović Balint, Milena; Bošković Matić, Tatjana (Vojnosanitetski pregled, 2025)
Background/Aim. Standard treatment for immune-mediated neurologic disorders (IMNDs) involves the use of immunosuppressive drugs and other therapies. Therapeutic plasma exchange (TPE) is an effective supplementary immunomodulatory approach. Its main goal is to decrease patients’ load of pathogenic factors (including autoantibodies) to the levels that will allow clinical improvement. Immunosuppressive medications used simultaneously with TPE reduce the “rebound rise” of autoantibody synthesis. The aim of the study was to evaluate the effectiveness of our own standardized TPE protocol and determine the correlation of TPE treatment outcomes with paraclinical (laboratory) and apheresis parameters/data. Methods. The study included 32 patients with myasthenia gravis, Guillain-Barré syndrome or acute polyradiculoneuropathy, and multiple sclerosis. TPEs were carried out using Spectra-Optia® (Terumo-BCT, USA). Properties of our apheresis protocol used for IMND patients were as follows: a) total treatment – five single TPE procedures; b) TPE frequency – every other day; c) removed plasma – one patient’s circulating plasma volume (range 2,800–3,100 mL). TPE effectiveness was determined based on recovery of neurologic deficiency and peripheral nerve conduction, positive findings in some paraclinical (laboratory) tests, and apheresis data monitoring. Results. Using the described apheresis protocol, a clear positive therapeutic effect was observed in patients treated by TPE procedures with no interruption. TPEs were advantageous in 84.4% of patients (effectiveness rate 89.3%; non-response rate 10.7%), while in 15.6% of cases, treatment was not completed due to patients’ severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (followed by coronavirus disease 19 – COVID-19). Patients who completed five single TPEs had evident clinical improvement in terms of disability scale, muscle weakness, or neural conduction deficit. In the follow-up period, no relapses were observed. Significantly reduced values of erythrocyte parameters (especially hematocrit levels) were correlated with higher TPE effectiveness, due to increased plasma/blood cell volume ratio, followed by higher plasma-collection/removal efficacy. Other examined laboratory findings did not show a positive correlation with TPE effectiveness/productivity. Severe adverse events did not occur. There were no relapses in the following 6 months. Conclusion. In this study, the reduced levels of erythrocyte parameters (particularly hematocrit levels) were associated with an increased TPE effectiveness. For definitive conclusions, further randomized and larger clinical investigations are needed
Keywords: blood component removal; guillain-barre syndrome; myasthenia gravis; multiple sclerosis; treatment outcome